Auditory Evoked Potential (AEP) Based Brain-Computer Interface (BCI) Technology: A Short Review - Islam, Md Nahidul; Norizam, Sulaiman; Bari, Bifta Sama; Rashid, Mamunur; Mahfuzah, Mustafa (Springer, 2021)
Auditory evoked potential (AEP) is a sort of electroencephalographic (EEG) signal elicited by an acoustic stimulus from the brain scalp. An intelligent auditory perception level system helps the auditory system to analyze and assess its functional integrity. Initially, the AEP signals are utilized in accurate and fast hearing threshold level detection in early stage. However, this emerging psychological modality expands it applications like other EEG control signals. Recently, AEP responses are initiated into the brain-computer technology (BCI) technology. This paper presents a short review on AEP based BCI technology. First, a concise overview of AEP signal and its analysis procedure are discussed. Then the existing AEP based studies are reviewed and their summary in terms of data description, feature extraction, classification methods and performance are tabulated. Finally, the issues of the recent AEP signal analysis have been addressed and potential ways are suggested to alleviate existing problems. Finally, the issues to the existing AEP based BCI technology are presented, and the possible solutions are also recommended.